Predicting metabolic syndrome by anthropometric measures among adults 35–65 years in the west of Iran; a cross sectional study from an Iranian RaNCD cohort data. Issue 5 (September 2020) - Hamzeh, Behrooz; Bagheri, Amir; Pasdar, Yahya; Darbandi, Mitra; Rezaeian, Shahab; Najafi, Farid; Moradinazar, Mehdi
Abstract: Aims: Anthropometric indices have been proposed for the early detection of metabolic syndrome (MetS) and its risk factors. The present study aimed to determine optimal cutoff points for the Body Mass Index (BMI), Waist Circumference (WC), and Waist Hip Ratio (WHR) in the prediction of MetS. Methods: This cross-sectional study was performed on 9746 adults 35–65 years, recruited in Ravansar Non-Communicable Diseases (RaNCD) cohort. The receiver operating characteristic (ROC) curve analysis was used to compare the predictive validity and determine optimal cutoff values. Results: The optimal cutoff points for BMI, WC and WHR were 27.3 kg/m 2 (AUC: 78.6; 95%CI 77.1, 80.1), 97 cm (AUC: 63.8; 95%CI 60.4, 67.2) and 0.95 (AUC: 75.5; 95% CI 73.9, 77.1), respectively in men for the prediction of MetS. But in women the optimal cutoff points for BMI, WC and WHR were 28.6 kg/m 2 (AUC: 65.7; 95%CI 62.1, 69.4), 98.1 cm (AUC: 65.6; 95%CI 62.4, 68.8) and 0.95 (AUC:62.39; 95%CI 60.9, 63.9). The risk of MetS in men and women with a BMI higher than the optimal cutoff point was respectively 2.23 and 2.30 times higher than that in those with a WC lower than the cutoff point. Conclusions: BMI is a better predictor of MetS than WC and WHR in adults 35–65 years. We recommend that the optimal cut off point be set for men 27.3 kg/m 2 and for women 28.6 kg/m 2 . Highlights: BMI is a better predictor for MetS than WC and WHR among adults 35–65 years in Iran. The optimal cut-off points of BMI for the men 27.3 kg/m 2 and 28.6 kg/m 2 in the women. The optimal cut-off point of WC for the men be set at 97 cm and the women at 98.1 cm.